COMBINATION OF TRANSITOR HYPERAMMONIEMIA WITH POST-HYPOXIC SYNDROME IN NEWBORN - Yulaeva Irina Andreevna (Scholar Express Journals, 2023)
Reactions that reflect the process of adaptation to childbirth, new living conditions, are called borderline (transitional, transient, physiological) states of newborns. The day of these conditions, in contrast to the anatomical and physiological characteristics of the newborn, is characterized by the fact that they appear during childbirth or after birth and then disappear. They are called borderline not only because they occur at the border of two periods of life (intrauterine and extrauterine), but also because they are usually physiological for newborns, under certain conditions they can take on pathological features. [1, 3, 9, 10, 17] The literature describes more than 50 such transient reactions affecting the metabolism and functioning of all systems, including: transient hyperammonemia. [2, 4, 5, 14, 16]
Keywords: Borderline conditions; transient hyperammonemia; nitrogen balance; posthypoxic syndrome